Olympic Movement Based Pencak Silat Training Model Block and Random Methods - Putra, Jeki Purnama; Astuti, Puji; Giovanni, Krisno; Candra, Oki; Gustiawati, Resty (JUMORA: Jurnal Moderasi Olahraga, 2025)
The crisis in value education in sport is increasingly evident, with many athletes prioritizing winning over the application of Olympic values. The paradigm shift from merely pursuing “sporting results” to “growing social impact” is the basis for understanding the importance of sport as a means of social development and improving the quality of life of the community. This research offers a new approach by integrating an Olympic Movement-based pencak silat training model, so that fighters/athletes gain a more comprehensive understanding of Olympic Movement values. This study used an experimental method with 45 participants divided into three groups: 15 participants in the Olympic Movement-based pencak silat training block method group, 15 participants in the random method group, and 15 participants in the control group. The instrument used was the Olympic Movement Instrument (OMI). The results showed a difference in the effect on the understanding of Olympic Movement values in each group. The group that practiced using the Olympic Movement-based model with block and random methods showed better results than the group that did not use the model. In conclusion, the Olympic Movement based pencak silat model that emphasizes the values of respect, friendship, and excellence with a deliberate structure has proven effective in improving understanding of Olympic Movement values and shaping the character of fighters. This model is considered feasible to use in athlete development